PENGEMBANGAN MANAJEMEN PARIWISATA ERA NEW NORMAL DI UMBUL PENGGING KECAMATAN BANYUDONO KABUPATEN BOYOLALI - Pertiwi Oktavia Setyaningtyas; Kismartini Kismartini; Amni Zarkasyi R (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
The Covid-19 pandemic has had an impact on several sectors, one of them being the tourism sector. This is also felt by the Tourism Object in Boyolali Regency, namely the Pengging Umbul Tourism Object. The purpose of this research was to analyze the development of tourism management in the new normal era at the Umbul Pengging tourist attraction in Boyolali Regency and identify the driving and inhibiting factors in tourism development in Boyolali Regency in the New Normal era. This research method is a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The results of research related to attractions, namely the building still has a royal nuance, original springs, the existence of kungkum customs and padusan ceremonies. The types of activities that can be carried out are swimming, culinary, therapy and outbound. Accessibility, namely the road network, geographical position, places to eat, access to ATMs, access to entertainment and availability of public transportation. Amenities, namely the facilities in Umbul Pengging. There are driving factors and inhibiting factors in the process of developing the Umbul Pengging tourist attraction. Recommendations that can be given are the need for additional types of public transportation, adding playgrounds and sports, the need to collaborate with local residents in the development process, the need for increased promotion, the need for activities such as shows or festivals held regularly and parties Managers need to pay attention to security in Umbul Pengging